2020
DOI: 10.3390/antiox9101028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selenium- and Zinc-Enriched Lactobacillus plantarum SeZi on Antioxidant Capacities and Gut Microbiome in an ICR Mouse Model

Abstract: Selenium and zinc are essential trace minerals for humans with various biological functions. In this study, selenium- and zinc-tolerant lactic acid bacteria (LAB) isolates were screened out from human fecal samples. Amongst three hundred LAB isolates, the Lactobacillus plantarum SeZi strain displayed the tolerance against selenium and zinc with the greatest biomass production and bioaccumulation of selenium and zinc. To further assess the characteristics of this strain, the lyophilized L. plantarum SeZi were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…In a further study, the Se content in the liver of animals fed a diet fortified with Se-enriched Bifidobacterium longum was much higher than that of animals fed a selenite-enriched diet [29]. Se-and Zn-enriched probiotics might thus be applied as promising functional food ingredients in the future [135]. Probiotics enriched with Se and Zn possibly increase bioavailability and absorption when compared with their inorganic forms, thus opening up another application for probiotics [153].…”
Section: Interaction Of Selenium and Probioticsmentioning
confidence: 85%
See 1 more Smart Citation
“…In a further study, the Se content in the liver of animals fed a diet fortified with Se-enriched Bifidobacterium longum was much higher than that of animals fed a selenite-enriched diet [29]. Se-and Zn-enriched probiotics might thus be applied as promising functional food ingredients in the future [135]. Probiotics enriched with Se and Zn possibly increase bioavailability and absorption when compared with their inorganic forms, thus opening up another application for probiotics [153].…”
Section: Interaction Of Selenium and Probioticsmentioning
confidence: 85%
“…The gastrointestinal microbiota has been shown to affect Se status and selenoprotein expression in mice [148] and is able to sequester Se and to restrict its availability to the host [149]. Bacteria may compete with the host for Se when availability becomes limiting [148], although, in the mouse model, Lactobacillus plantarum enriched with Se and Zn increases antioxidant activity and blood Se levels [135]. In the study of Krausova et al [27], the administration of Se-enriched lactic acid bacteria (Streptococcus thermophilus and Enterococcus faecium) improved the antioxidant status of the rats.…”
Section: Interaction Of Selenium and Probioticsmentioning
confidence: 99%
“…Also, González-Olivares et al 56 detected that the lactic acid bacteria can survive in concentrations over 200 mg/L of Na 2 SeO 3 . Kang et al 57 indicated for lactobacilli species grew in the presence of 60 mM selenite, including Lb. plantarum, Lb.…”
Section: Resultsmentioning
confidence: 99%
“…Recent experiments with probiotic isolates permitted bioaccumulation of selenium and zinc in the blood of mice fed with the selenium- and zinc-enriched lactobacillus strain. The fact that the animals also showed increased antioxidant capacities indicates new perspectives in mineral-induced modulation of the redox status [ 62 ].…”
Section: Mineral Elements In Skin Homeostasismentioning
confidence: 99%